Low-rebound high-performance shotcrete based on composite cementitious system and construction method
Patent Information
- Application Number
- CN202410488094.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-23
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-04-23
AI Technical Summary
[0004]检索发现公布号CN114671644A公布了一种高早强低回弹的高性能喷射混凝土及其制备方法,实施例的喷射混凝土的早期强度较好,回弹率较低,但对于喷射混凝土粘结强度没有提及,也没有抗渗性、抗冻性及抗冲磨性能的数据,无法在严寒地区水工隧洞中直接应用
Smart Images

Figure CN118388196B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of shotcrete, and in particular relates to low-rebound high-performance shotcrete based on a composite gelling system and a construction method. Background Art
[0002] In recent years, the investment in water conservancy engineering diversion tunnels and highway tunnel projects is relatively large, so shotcrete support projects have been widely used. Shotcrete is a concrete that uses compressed air to spray concrete mixtures at high speed onto the working surface and compact it. Compared with ordinary concrete, shotcrete has fast construction speed, simple process, high early strength of concrete, and low cost. In particular, the construction operation method is flexible. It can make thin-walled or complex structures in any direction at high altitudes, deep pits or narrow working areas. The construction area is small and flexible. Its superiority is particularly obvious in irregular components and projects where it is inconvenient to use formwork. However, there are also some problems at present, such as the deterioration of sand and gravel materials, uneven quality of quick-setting agent products, high grade of surrounding rock, and serious over-excavation. The deterioration of materials makes it difficult to control the state of shotcrete. The uneven quality of quick-setting agent products, high grade of surrounding rock, and serious over-excavation will lead to a large actual rebound of shotcrete. According to statistics, the rebound rate of conventional shotcrete is greater than 20%, and the maximum rebound rate even exceeds 45%. This situation not only increases the cost, but also prolongs the construction period, and has a great impact on construction safety. How to effectively reduce the rebound rate of shotcrete has become the most critical issue in the field of tunnel construction. In addition, tunnels and shafts that are subject to high-speed water flow erosion or ore impact wear should have corresponding anti-abrasion performance, and in permanent shotcrete projects with severe freeze-thaw erosion, the anti-freeze-thaw cycle capacity of shotcrete should not be less than 200 times, so it is very necessary to improve the comprehensive performance of shotcrete.
[0003] A search revealed that publication number CN115478880A discloses a construction method for reducing the rebound rate of shotcrete. The early strength of shotcrete is improved by adding a mixture fusion agent and controlling the construction method. However, there is no description of the effect of reducing the rebound rate. There is no other specific data except the strength, and the actual effect is unknown.
[0004] A search revealed that publication number CN114671644A discloses a high-early-strength, low-rebound high-performance shotcrete and a preparation method thereof. The shotcrete in the embodiment has good early strength and low rebound, but there is no mention of the bond strength of the shotcrete, and there is no data on the impermeability, frost resistance and abrasion resistance, so it cannot be directly applied in hydraulic tunnels in severely cold areas.
[0005] Based on the above deficiencies, the rebound rate of shotcrete is reduced, the early strength of shotcrete is improved, the bonding strength between concrete and rock foundation is improved, and the impermeability, frost resistance and abrasion resistance of shotcrete are improved to facilitate the application of shotcrete in water conservancy engineering tunnels.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:
[0008] Low-resilience high-performance shotcrete based on a composite cementitious system comprises a shotcrete main material and an interface treatment mortar; the shotcrete main material is composed of the following raw materials (by weight):
[0009] 1000 parts of ordinary Portland cement, 50-100 parts of high alumina cement, 100-150 parts of fly ash, 20-30 parts of silica fume, 2100-2300 parts of sand, 210-230 parts of stone powder, 2100-2300 parts of small stones, 1-2 parts of instant glue powder, 1-2 parts of hydroxypropyl methylcellulose, 1.5-2.0 parts of basalt fiber, 8-12 parts of high-performance water reducer, 20-30 parts of accelerator, 170-190 parts of mixing water;
[0010] The interface treatment mortar is composed of the following raw materials (by weight):
[0011] 1000 parts of ordinary Portland cement, 50-100 parts of high alumina cement, 1000-1200 parts of sand, 1-2 parts of instant glue powder, 1-2 parts of hydroxypropyl methylcellulose, 20-30 parts of accelerating agent, and 350-400 parts of mixing water.
[0012] As a preferred embodiment of the present invention, the cement is any one of ordinary Portland cement P.O42.5 and P.O52.5 cement.
[0013] As a preferred embodiment of the present invention, the high-alumina cement is aluminate cement, and the model is any one of CA50 and CA70; the fly ash is any one of Class F 2 ash or Class F 1 ash.
[0014] As a preferred embodiment of the present invention, the SiO2 content in the silicon powder is greater than 85%, and the surface area is greater than 15000m2 / kg.
[0015] As a preferred embodiment of the present invention, the coarse aggregate is any one of crushed stone or pebbles, and the particle size is 5-10 mm.
[0016] As a preferred embodiment of the present invention, the sand is any one of natural sand or artificial sand; the specification is medium sand.
[0017] As a preferred embodiment of the present invention, the instant gel powder is any one of 801 instant gel powder and 901 instant gel powder; the hydroxypropyl methylcellulose has a viscosity of 200,000 or more.
[0018] As a preferred embodiment of the present invention, the basalt fiber has a single-filament diameter of 13 μm and a length of 3 mm or 6 mm.
[0019] As a preferred embodiment of the present invention, the high-performance water-reducing agent is a polycarboxylic acid water-reducing agent; the accelerating setting agent is an alkali-free accelerating setting agent or a low-alkali accelerating setting agent.
[0020] The present invention also discloses a construction method of low-resilience high-performance shotcrete based on a composite gelling system, comprising the following steps:
[0021] Step S1, base surface treatment: excavation of rock base surface and measurement of cross-sectional dimensions;
[0022] Step S2, troubleshoot hidden dangers: remove pumice and loose stones, and drain and treat areas with severe water seepage; finally, rinse with a high-pressure water gun and clean the contaminated work surface;
[0023] Step S3, preparing interface treatment mortar: 1000 parts of ordinary Portland cement, 50-100 parts of high alumina cement, 1000-1200 parts of sand, 1-2 parts of instant glue powder, 1-2 parts of hydroxypropyl methylcellulose, and 350-400 parts of mixing water are stirred into a mortar mixture;
[0024] Step S4, spraying interface treatment mortar: 20-30 parts of accelerator are added at the nozzle. The spraying operation should be carried out in sections and sections, and should be constructed from bottom to top in the order of spraying the side surface first and then the top surface, with a spraying thickness of 2mm;
[0025] Step S5, preparing low-resilience high-performance shotcrete, putting 1000 parts of ordinary Portland cement, 50-100 parts of high-alumina cement, 100-150 parts of fly ash, 20-30 parts of silica fume, 2100-2300 parts of sand, 210-230 parts of stone powder, 2100-2300 parts of small stones, 1-2 parts of instant glue powder, 1-2 parts of hydroxypropyl methylcellulose, 1.5-2.0 parts of basalt fiber, 8-12 parts of high-performance water reducer, and 170-190 parts of mixing water into a mixer, using forced stirring, and the stirred mixture should be sprayed within 1-1.5 hours;
[0026] Step S6, spraying of low-resilience high-performance concrete, spraying operation starts after the sprayed interface treatment mortar is finally set, and 20-30 parts of accelerator are added at the nozzle; the spraying operation should be carried out in pieces and sections, and the construction is still carried out from bottom to top in the order of spraying the side surface first and then the top surface; the thickness of the first spraying is also 10-30mm, and the thickness of the second spraying is also 20-40mm. The latter layer of spraying should be carried out 5-10 minutes after the final setting of the previous sprayed concrete. If spraying is carried out again after 1 hour of final setting, the surface of the previous spraying layer should be cleaned with wind and water before the next spraying operation;
[0027] Step S7, curing of shotcrete, water spraying curing should start 2 hours after final setting, the curing time shall not be less than 7 days, and for important projects, it shall not be less than 14 days.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The ordinary silicate cement and high-aluminum cement of the present invention are mixed and used to greatly improve the early strength of concrete. Since high-aluminum cement can shorten the setting time, the amount of accelerator can be saved after being added; fly ash can replace part of the cement, improve the workability of the mixture, and can also improve the later strength of the shotcrete; the addition of silicon powder can improve the strength, antifreeze and anti-abrasion performance of the shotcrete. The combination of instant glue powder and hydroxypropyl methylcellulose can improve the cohesiveness of the shotcrete mixture, effectively reduce the rebound rate of the shotcrete, and improve the bonding strength of the concrete. In addition, the addition of instant glue powder can form a continuous film inside the concrete, which can improve the impermeability of the shotcrete and also improve the antifreeze property of the shotcrete. The addition of stone powder can improve the workability of the shotcrete, increase the density, and then improve the strength of the concrete. The stone powder is processed from rocks mined by tunnel excavation, which reduces the production cost. The addition of basalt fiber improves the anti-abrasion and cracking resistance of the concrete. The spraying of interface treatment mortar improves the bonding strength and compressive strength between shotcrete and rock or base surface, and avoids the fall of shotcrete, especially the concrete of the top arch.
[0030] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In the attached picture:
[0032] Figure 1 It is a schematic diagram of the construction process of the present invention. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. The following embodiments are used to illustrate the present invention.
[0034] Embodiment 1:
[0035] Before construction, spray large molds, spray large panels and impact and abrasion resistance tests should be carried out.
[0036] Spraying large mold test: 1000 parts of ordinary Portland cement, 50 parts of high alumina cement, 1000 parts of sand, 1 part of instant glue powder, 1 part of hydroxypropyl methylcellulose, and 350 parts of mixing water are stirred into a mortar mixture. 20 parts of accelerator are added at the nozzle to start spraying mortar into an open large mold (size 450×350×120mm). Rock blocks (about 400×300×50mm) selected from the project site are placed in the large mold. After spraying, they are cured for 28 days under the same conditions as the construction, and cut into 100×100×100mm cubic specimens. The bonding strength of the sprayed concrete and rock interface is obtained by the splitting method along the interface between the sprayed concrete and the rock.
[0037] Large board spraying test: put 1000 parts of ordinary Portland cement, 50 parts of high alumina cement, 100 parts of fly ash, 20 parts of silica powder, 2100 parts of sand, 210 parts of stone powder, 2100 parts of small stones, 1 part of instant glue powder, 1 part of hydroxypropyl methylcellulose, 1.5 parts of basalt fiber, 8 parts of high-performance water reducer and 170 parts of mixing water into a mixer and use forced stirring. After stirring, start spraying the large board. 20 parts of quick-setting agent are added at the nozzle. The size of the large board wood mold is 450×350×200mm. After spraying, it is cured for 28 days under the same conditions as the construction. It is cut into 100×100×100mm compression test pieces in a group of 3 and 400×100×100mm antifreeze test pieces in a group of 3. For the anti-seepage test pieces, drill 6 cylindrical test pieces with a diameter and height of 150mm on the large board, and carry out compression, antifreeze and anti-seepage tests respectively.
[0038] Anti-impact and abrasion test: spray the large plate mixture into the anti-impact and abrasion test mold (size is 300mm diameter, 100mm high flat cylinder) in groups of 3. After spraying, maintain it for 28 days under the same conditions as the construction, and use the underwater steel ball method to carry out the anti-impact and abrasion test.
[0039] Spraying operation: The spraying test was started in the engineering test section, and the rebound rate was calculated by the spraying volume and the rebound volume. The results are shown in Table 1.
[0040] Table 1 Test results of Example 1
[0041]
[0042] Embodiment 2:
[0043] The steps of spraying large molds, spraying large plates and anti-impact and abrasion tests are the same as those in Example 1.
[0044] Spraying large mold test: 1000 parts of ordinary Portland cement, 75 parts of high alumina cement, 1100 parts of sand, 1 part of instant glue powder, 2 parts of hydroxypropyl methylcellulose, and 375 parts of mixing water are stirred into a mortar mixture. 30 parts of accelerator are added at the nozzle to start spraying mortar into an open large mold (size 450×350×120mm). Rock blocks (about 400×300×50mm) selected from the project site are placed in the large mold. After spraying, they are cured for 28 days under the same conditions as the construction, and cut into 100×100×100mm cubic specimens. The bonding strength of the sprayed concrete and rock interface is obtained by the splitting method along the interface between the sprayed concrete and the rock.
[0045] Large board spraying test: put 1000 parts of ordinary Portland cement, 75 parts of high alumina cement, 125 parts of fly ash, 25 parts of silica fume, 2200 parts of sand, 220 parts of stone powder, 2200 parts of small stones, 1 part of instant glue powder, 2 parts of hydroxypropyl methylcellulose, 2 parts of basalt fiber, 10 parts of high-performance water reducer and 180 parts of mixing water into a mixer and use forced stirring. After stirring, start spraying the large board. 30 parts of accelerator are added at the nozzle. The size of the large board wood mold is 450×350×200mm. After spraying, it is cured for 28 days under the same conditions as the construction. It is cut into 100×100×100mm compression test pieces in a group of 3 and 400×100×100mm antifreeze test pieces in a group of 3. For the anti-seepage test pieces, drill 6 cylindrical test pieces with a diameter and height of 150mm on the large board, and carry out compression, antifreeze and anti-seepage tests respectively.
[0046] Anti-impact and abrasion test: spray the large plate mixture into the anti-impact and abrasion test mold (size is 300mm diameter, 100mm high flat cylinder) in groups of 3. After spraying, maintain it for 28 days under the same conditions as the construction, and use the underwater steel ball method to carry out the anti-impact and abrasion test.
[0047] Spraying operation: The spraying test was started in the engineering test section, and the rebound rate was calculated by the spraying volume and the rebound volume. The results are shown in Table 2.
[0048] Table 2 Test results of Example 2
[0049]
[0050]
[0051] Embodiment 3:
[0052] The steps of spraying large molds, spraying large plates and anti-impact and abrasion tests are the same as those in Example 1.
[0053] Spraying large mold test: 1000 parts of ordinary Portland cement, 100 parts of high alumina cement, 1200 parts of sand, 2 parts of instant glue powder, 2 parts of hydroxypropyl methylcellulose, and 400 parts of mixing water are stirred into a mortar mixture. 30 parts of accelerator are added at the nozzle to start spraying mortar into an open large mold (size 450×350×120mm). Rock blocks (about 400×300×50mm) selected from the project site are placed in the large mold. After spraying, they are cured for 28 days under the same conditions as the construction, and cut into 100×100×100mm cubic specimens. The bonding strength of the sprayed concrete and rock interface is obtained by the splitting method along the interface between the sprayed concrete and the rock.
[0054] Large board spraying test: put 1000 parts of ordinary Portland cement, 100 parts of high alumina cement, 150 parts of fly ash, 30 parts of silica powder, 2300 parts of sand, 230 parts of stone powder, 2300 parts of small stones, 2 parts of instant glue powder, 2 parts of hydroxypropyl methylcellulose, 2 parts of basalt fiber, 12 parts of high-performance water reducer and 190 parts of mixing water into a mixer and use forced stirring. After stirring, start spraying the large board. 30 parts of accelerator are added at the nozzle. The size of the large board wood mold is 450×350×200mm. After spraying, it is cured for 28 days under the same conditions as the construction. It is cut into 100×100×100mm compression test pieces in a group of 3 and 400×100×100mm antifreeze test pieces in a group of 3. For the anti-seepage test pieces, drill 6 cylindrical test pieces with a diameter and height of 150mm on the large board, and carry out compression, antifreeze and anti-seepage tests respectively.
[0055] Anti-impact and abrasion test: spray the large plate mixture into the anti-impact and abrasion test mold (size is 300mm diameter, 100mm high flat cylinder) in groups of 3. After spraying, maintain it for 28 days under the same conditions as the construction, and use the underwater steel ball method to carry out the anti-impact and abrasion test.
[0056] Spraying operation: The spraying test was started in the engineering test section, and the rebound rate was calculated by the spraying volume and the rebound volume. The results are shown in Table 3.
[0057] Table 3 Test results of Example 3
[0058]
[0059] It can be seen from the embodiments that the early strength and 28-day strength of the low-rebound shotcrete based on the composite cementitious system provided by the present invention are both high, which meet the technical requirements of shotcrete; the impermeability grade is greater than W12, which meets the technical requirements of water conservancy projects; the anti-freeze cycle is greater than 200 times, which meets the needs of permanent shotcrete projects in water conservancy projects with severe freeze-thaw erosion; the impact and abrasion resistance is 19.2-21.8 kg / m2, and the impact and abrasion resistance is much better than that of ordinary concrete, which meets the needs of tunnel projects subjected to high-speed water flow erosion or ore impact wear; the splitting tensile strength is not less than 2MPa, indicating that the bonding strength is also good, which fully meets the bonding requirements of concrete and rock base; the rebound rates of the side wall spraying in the three embodiments are all lower than 6%, and the rebound rates of the top arch spraying in Embodiment 2 and Embodiment 3 are both lower than 10%, which shows that the concrete is a shotcrete with low rebound and excellent performance.
[0060] Working principle: In order to achieve low rebound and high performance of shotcrete, the material consists of the main material of shotcrete and interface treatment mortar. The main material of shotcrete introduces a diversified composite cementitious system, which consists of ordinary Portland cement-high alumina cement-fly ash-silica powder to form a composite cementitious material. The mixing of ordinary Portland cement and high alumina cement can greatly improve the early strength of concrete. Since high alumina cement can shorten the setting time, the amount of accelerator can be saved after adding it; fly ash can replace part of the cement, improve the workability of the mixture, and also improve the later strength of shotcrete; the addition of silica powder can improve the strength, antifreeze and anti-abrasion properties of shotcrete. The combination of instant glue powder and hydroxypropyl methylcellulose can improve the cohesion of the shotcrete mixture, effectively reduce the rebound rate of shotcrete, and improve the bonding strength of concrete. In addition, the addition of instant glue powder can form a continuous film inside the concrete, which can improve the impermeability of shotcrete and also improve the antifreeze property of shotcrete. The addition of stone powder can improve the workability of shotcrete, increase density, and thus increase concrete strength. Stone powder is processed from rocks mined during tunneling, which reduces production costs. The addition of basalt fiber improves the abrasion resistance and crack resistance of concrete. The spraying of interface treatment mortar improves the bonding strength and compressive strength between shotcrete and rock or base surface, and prevents the fall of shotcrete, especially the concrete of the top arch.
Claims
1. Low-resilience high-performance shotcrete based on a composite cementitious system, including shotcrete main material and interface treatment mortar, characterized in that: The main material of shotcrete is composed of the following raw materials: 1000 parts of ordinary Portland cement, 50-100 parts of high alumina cement, 100-150 parts of fly ash, 20-30 parts of silica fume, 2100-2300 parts of sand, 210-230 parts of stone powder, 2100-2300 parts of small stones, 1-2 parts of instant glue powder, 1-2 parts of hydroxypropyl methylcellulose, 1.5-2.0 parts of basalt fiber, 8-12 parts of high-performance water reducer, 20-30 parts of accelerator, 170-190 parts of mixing water; The interface treatment mortar is composed of the following raw materials: 1000 parts of ordinary Portland cement, 50-100 parts of high alumina cement, 1000-1200 parts of sand, 1-2 parts of instant glue powder, 1-2 parts of hydroxypropyl methylcellulose, 20-30 parts of accelerating agent, and 350-400 parts of mixing water.
2. The low-resilience high-performance shotcrete based on the composite cementitious system according to claim 1 is characterized in that: The ordinary Portland cement is any one of ordinary Portland cement P.O42.5 and P.O52.5 cement.
3. The low-resilience high-performance shotcrete based on the composite cementitious system according to claim 1 is characterized in that: The high-alumina cement is aluminate cement, and the model is any one of CA50 and CA70; the fly ash is any one of Class F 2 ash or Class F 1 ash.
4. The low-resilience high-performance shotcrete based on the composite cementitious system according to claim 1, characterized in that: The SiO2 content of the silicon powder is greater than 85%, and the surface area is greater than 15000m2 / kg.
5. The low-resilience high-performance shotcrete based on the composite cementitious system according to claim 1, characterized in that: The small stones are any one of crushed stones or pebbles, and the particle size is 5-10mm.
6. The low-resilience high-performance shotcrete based on a composite cementitious system according to claim 1, characterized in that: The sand is any one of natural sand or artificial sand; the specification is medium sand.
7. The low-resilience high-performance shotcrete based on a composite cementitious system according to claim 1, characterized in that: The instant glue powder is any one of 801 instant glue powder and 901 instant glue powder; the viscosity of the hydroxypropyl methylcellulose is above 200,000.
8. The low-resilience high-performance shotcrete based on a composite cementitious system according to claim 1, characterized in that: The basalt fiber has a single-filament diameter of 13 μm and a length of 3 mm or 6 mm.
9. The low-resilience high-performance shotcrete based on a composite cementitious system according to claim 1, characterized in that: The high-performance water-reducing agent is a polycarboxylic acid water-reducing agent; the accelerating setting agent is an alkali-free accelerating setting agent or a low-alkali accelerating setting agent.
10. A construction method of low-resilience high-performance shotcrete based on a composite cementitious system, applied to the low-resilience high-performance shotcrete based on a composite cementitious system as claimed in claim 1, characterized in that: The following steps are involved: Step S1, base surface treatment: excavation of rock base surface and measurement of cross-sectional dimensions; Step S2, troubleshoot hidden dangers: remove pumice and loose stones, and drain and treat areas with severe water seepage; finally, rinse with a high-pressure water gun and clean the contaminated work surface; Step S3, preparing interface treatment mortar: 1000 parts of ordinary Portland cement, 50-100 parts of high alumina cement, 1000-1200 parts of sand, 1-2 parts of instant glue powder, 1-2 parts of hydroxypropyl methylcellulose, and 350-400 parts of mixing water are stirred into a mortar mixture; Step S4, spraying interface treatment mortar: 20-30 parts of accelerator are added at the nozzle; the spraying operation should be carried out in pieces and sections, and the construction should be carried out from bottom to top in the order of spraying the side surface first and then the top surface, and the spraying thickness is 2mm; Step S5, preparing low-resilience high-performance shotcrete, putting 1000 parts of ordinary Portland cement, 50-100 parts of high-alumina cement, 100-150 parts of fly ash, 20-30 parts of silica fume, 2100-2300 parts of sand, 210-230 parts of stone powder, 2100-2300 parts of small stones, 1-2 parts of instant glue powder, 1-2 parts of hydroxypropyl methylcellulose, 1.5-2.0 parts of basalt fiber, 8-12 parts of high-performance water reducer, and 170-190 parts of mixing water into a mixer, using forced stirring, and the stirred mixture should be sprayed within 1-1.5 hours; Step S6, spraying of low-resilience high-performance concrete, spraying operation starts after the sprayed interface treatment mortar is finally set, and 20-30 parts of accelerator are added at the nozzle; the spraying operation should be carried out in pieces and sections, and the construction is still carried out from bottom to top in the order of spraying the side surface first and then the top surface; the thickness of the first spraying is also 10-30mm, and the thickness of the second spraying is also 20-40mm. The latter layer of spraying should be carried out 5-10 minutes after the final setting of the previous sprayed concrete. If spraying is carried out again after 1 hour of final setting, the surface of the previous spraying layer should be cleaned with wind or water before the next spraying operation; Step S7, curing of shotcrete, water spraying curing should start 2 hours after final setting, the curing time shall not be less than 7 days, and for important projects, it shall not be less than 14 days.
Citation Information
Patent Citations
Construction method for reducing springback rate of sprayed concrete
CN115478880A
Ultrahigh-toughness cement-based composite material used in ejection, and ejection process thereof
CN104150845A
Hydraulic concrete high-performance repair mortar and construction process thereof
CN117822933A